Handbook of research on civil society and national security in the era of cyber warfare - Hadji-Janev, Metodi; Bogdanoski, Mitko (Advances in digital crime, forensics, and cyber terrorism (ADCFCT), 2016)
This book addresses the problem of cyber terrorism head-on, first through a review of current literature, and then through a series of progressive proposals aimed at researchers, professionals, and policymakers.